(untitled) (Research, Society and Development, 2023)
This study aimed to analyze the exposure and sun protection of medical students at a private university in a northeastern capital city. This was a cross-sectional, descriptive, observational and quantitative study, which was developed with medical students who have taken the discipline of dermatology at the Unifacid University Center. It was verified a higher prevalence of sunscreen use among females, with 75 (61.5%) cases, aged between 18 and 25 years, 75 (61.5%), single 110 (90.7%), and 49 (40.2%) had family income of 10 to 15 minimum wages. About 72 (59.02%) individuals reported white skin color, 93 (76.23%) reported having dark brown eyes, and 57 (46.72%) reported having dark brown hair. About 72 (59.1%) of the students interviewed reported using sunscreen daily, however, most reported not using it, with a total of 42 (34.43%) respondents, about 25 (20.5%) used factor 30 SPF and 19 (15.6%) factor 50 SPF. In addition, about 74 (60.6%) said they used sunscreen 1 to 2x/day, more often in the morning and afternoon hours, 62 (50.82%). The use of sunscreen showed an increase according to the academic period attended, with about 12 (48.0%) of the students in the 5th period reporting the use of sunscreen and about 20 (69.0%) in the 9th period. Therefore, we noticed a greater use of sunscreen in individuals with a more advanced course period.